Adeno-associated virus (AAV) vectors: Rational design strategies for capsid engineering. (September 2018) - Lee, Esther J.; Guenther, Caitlin M.; Suh, Junghae
Abstract: Adeno-associated virus (AAV) consists of a simple genome, infects mammalian cells, displays nonpathogenicity in humans, and spans an array of serotypes and variants bearing distinct tissue tropisms. These attributes lend AAV tremendous promise as a gene delivery vector, further substantiated by its extensive testing in human clinical trials. Rational design approaches to capsid engineering leverage current scientific knowledge of AAV to further modulate, enhance and optimize the performance of the vectors. Capsid modification strategies include amino acid point mutations, peptide domain insertions, and chemical biology approaches. Through such efforts, insights regarding AAV capsid sequence-structure-function relationships can be learned. Developments over the last 5 years in rational design-based capsid engineering approaches will be presented and discussed. Graphical abstract: Highlights: Rational design of AAV relies on virus sequence, structure, and function knowledge. Strategies include point mutations, motif insertions, and chemical biology methods. Goals are to improve AAV transduction efficiency, specificity, and immune evasion.